2022
DOI: 10.1177/01600176221082308
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness, Complexity, and Economic Growth in Chinese Cities

Abstract: Innovation is generally regarded as critical to long-run economic growth. Recent work, at different spatial scales, suggests economies that develop more complex technologies that are related to their existing knowledge stocks enjoy a growth premium. Thus, “smarter” forms of innovation may accelerate growth. These claims are examined using Chinese patent data distributed across 286 cities over the period 1991–2015. Fixed-effects panel models report that city-level GDP growth in China has a significant and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 113 publications
0
7
0
1
Order By: Relevance
“…Economic growth. Economies with high levels of complexity relative to their GDP per capita are known to experience faster long-term economic growth [15][16][17][18][19][20][21][22][23][24] . The idea is that higher complexity economies can participate in sophisticated sectors that support higher wages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic growth. Economies with high levels of complexity relative to their GDP per capita are known to experience faster long-term economic growth [15][16][17][18][19][20][21][22][23][24] . The idea is that higher complexity economies can participate in sophisticated sectors that support higher wages.…”
Section: Resultsmentioning
confidence: 99%
“…Economic complexity methods provide a solution to this problem 13,14 by leveraging data on the geographic distribution of economic activities to estimate the implicit presence of multiple factors. These estimates have been validated by their ability to explain international variations in economic growth [15][16][17][18][19][20][21][22][23][24] , income inequality [25][26][27] , and emissions [28][29][30][31] . The reason why complexity metrics work is that they capture information about productive structures that escapes simple aggregate metrics, such as GDP or market concentration indexes.…”
mentioning
confidence: 99%
“…Intelligent technologies can complement existing services and reveal opportunities for the future development of smart destinations (Orden-Mejia & Huertas, 2022, Soares et al, 2022); many previous studies have shown that readiness to use intelligent technologies can affect satisfaction (Gretzel & Koo, 2021, Javadinasr et al, 2022). Intelligent technologies’ perceived ease of use and usefulness can increase tourists’ satisfaction with an enterprise’s various operations (Wu, Gursoy, & Zhang, 2021; Li & Rigby, 2023); intelligent technologies have become an indispensable part of tourism services.…”
Section: Research Modelsmentioning
confidence: 99%
“…Due to the fact that large cities have more high-quality human resources and higher absorption rates of new technologies, their innovation competitiveness is stronger than ordinary cities, thus occupying a circular advantage in the diffusion of innovation levels in the urban system [4,5]. In addition, relevant studies have shown that due to the advantages of infrastructure, transportation, and cultural atmosphere in large cities, new economic industries are more likely to emerge, which accelerates the agglomeration of innovative enterprises in the center of large cities, increases the growth space of enterprises, and further accelerates the diffusion of innovation space [6][7][8]. 2.…”
Section: Introductionmentioning
confidence: 99%